2013
DOI: 10.1002/ejlt.201200119
|View full text |Cite
|
Sign up to set email alerts
|

Camelina sativa affects the fatty acid contents in M. longissimus muscle of lambs

Abstract: Ruminant diets supplemented with different sources of unsaturated fatty acids (UFA) may be effective for modulating the rumen biohydrogenation process as well as for de novo fatty acid synthesis in animal tissues. Such a supplementation may consequently improve the proportion of fatty acids in animal products. The obtained effect in animal products depends on the quantity and composition of dietary fat; particularly UFAs. This study illustrates the effect of diets in which two doses of Camelina sativa (100 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
2
16
1
Order By: Relevance
“…Additionally, Santos-Silva et al (2002) showed that the proportion of CLA present in intramuscular fat was dependent on feeding system. While some researchers reported that CLA rates are higher than the rates found in this study (Garcia et al, 2008;Cieslak et al, 2013;Villalobos-Villalobos et al, 2014), others have indicated lower CLA rate in lamb genotypes (Santos-Silva et al, 2002;Yarali et al, 2014). Linoleic acid (n-6, C18:2) predominates among the PUFAs.…”
Section: Resultscontrasting
confidence: 67%
See 2 more Smart Citations
“…Additionally, Santos-Silva et al (2002) showed that the proportion of CLA present in intramuscular fat was dependent on feeding system. While some researchers reported that CLA rates are higher than the rates found in this study (Garcia et al, 2008;Cieslak et al, 2013;Villalobos-Villalobos et al, 2014), others have indicated lower CLA rate in lamb genotypes (Santos-Silva et al, 2002;Yarali et al, 2014). Linoleic acid (n-6, C18:2) predominates among the PUFAs.…”
Section: Resultscontrasting
confidence: 67%
“…Likewise, the proportion of conjugated linoleic acid (CLA) was also highest in KMM lambs (Table 2). Cieslak et al (2013) reported that the higher the conversion of CLA in muscle of lambs was presumably because of the conversion of vaccenic acid to CLA, by the enzymatic activity of 9 -desaturase. Additionally, Santos-Silva et al (2002) showed that the proportion of CLA present in intramuscular fat was dependent on feeding system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, less 16:0 was desaturated to cis-9 16:1 in the FIB treatment (P<0.05) compared with the other treatments (Table 2). Neither Lanza et al (2011) nor Cieslak et al (2013) observed changes on 12:0, 14:0, 16:0 and cis-9 16:1 concentrations in the IMF of lambs fed diets where camelina cake partially replaced rapeseed and soybean meal.…”
Section: Resultsmentioning
confidence: 69%
“…Some studies have reported the effects of replacing soybean meal with legume seeds on the intramuscular FA profile of lambs (Lanza et al, 2011;Scerra et al, 2011). The effects of replacing conventional protein sources by camelina cake or camelina seeds on the intramuscular FA profile of lambs were reported by Noci et al (2011) and Cieslak et al (2013), but no studies have dealt with the effects of solvent-extracted camelina meal. Solvent-extracted camelina meal has a lower fat content than camelina cake (3.0 vs. 13.6%).…”
Section: Introductionmentioning
confidence: 99%